Sustainable Alternatives to Asbestos in Brake Pads: Hybridization of Natural Fibres from Agro-Waste for Enhanced Mechanical and Tribological Performance: A Review - Friday A. ONUH; Tunde O. OGUNDANA; James O. ABIOYE; Kazeem A. BELLO (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
The global transition away from asbestos-based brake pads has driven extensive research into sustainable, high-performance alternatives. Asbestos, formerly valued for its exceptional thermal stability ansd durability, has been phased out due to its severe health risks, necessitating the development of non-toxic friction materials. This review explores alternative materials for brake pad manufacturing, with a particular focus on natural green fibres as filler materials, including coconut shells, rice husks, palm kernel shells, banana peels, and other plant-based fibres. These materials offer key advantages, such as biodegradability, cost-effectiveness, and environmental sustainability, while maintaining essential mechanical and thermal properties. Furthermore, the hybridization of these natural fibres to develop a superior, asbestos-free composite material for brake pad production has been investigated. The review examines recent advancements in material formulation and evaluates the potential for next-generation, eco-friendly brake pads. By integrating renewable resources, the automotive industry can enhance safety, reduce environmental impact, and align with international sustainability standards.